Short Communication: Phytochemical diversity and bioactivity of Malaysian Premna cordifolia (Lamiaceae): Chelation and protective activities of Premna cordifolia. - DZULSUHAIMI DAUD; MUHAMMAD SHAFIQ AZAMUDIN MD DEWA; EMI NORZEHAN MOHAMAD MAHBOB; WAN RAZARINAH WAN ABDUL RAZAK (Society for Indonesian Biodiversity, 2021)
Abstract. Daud D, Dewa MSAM, Mahbob ENM, Razak WRWA. 2021. Short Communication: Phytochemical diversity and bioactivity of Malaysian Premna cordifolia (Lamiaceae). Biodiversitas 22: 3245-3248. The aims of the present study are to determine the chelation potential and protective effect of Premna cordifolia leaves ethanolic extract in lead intoxicated mice. Twenty-four male mice were divided into four groups with six animals each. Group 1 was healthy mice and received 2 ml/kg bwt distilled water. Group 2 was healthy mice and supplemented with 200 mg/kg bwt P. cordifolia leaves ethanolic extract. Group 3 was lead intoxicated mice and received 2 ml/kg bwt distilled water. Group 4 was lead intoxicated mice and supplemented with 200 mg/kg bwt P. cordifolia leaves ethanolic extract. All treatments were given for 14 days. Chelation activity was determined by measuring the concentrations of lead in the liver, kidney and testis by using atomic absorption spectroscopy. Sperm quality was tested according to World Health Organization manual and testosterone was estimated by using ELISA kit. Spectroscopic data showed that P. cordifolia leaves ethanolic extract was able to lower lead concentrations in liver, kidney and testis of lead intoxicated mice. Following a decrease in lead concentrations, sperm quality and testosterone levels were restored in lead intoxicated mice supplemented with P. cordifolia leaves ethanolic extract. In conclusion, P. cordifolia leaves ethanolic extract has the potential to be developed as an alternative remedy for treating lead poisoning effects.